Analysis and quantification of air quality and climate co-benefits for coal-fired power plants in China - Chen, Jing; Nguyen, Thi Kim Oanh; Visvanathan, C.; Thammarat Koottatep; ADB-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
This research develops an emission inventory for coal-fired power plants in China and explores the relevant climate co-benefits of the pollution mitigation measures taken in different technology implementation scenarios. Using 2007 as the base year, an emission inventory of coal-fired power plants in China is developed and the emissions of SPM, PM10, PM2.5, OC, BC, COb2(B, SOb2(B, NOx and VOCs are estimated to be 2486 k ton, 1740 k ton, 870 k ton, 12.5 k ton, 0.1 k ton, 3888.6 million ton, 9758 k ton, 7413 k ton and 212 k ton respectively. The co-benefits are analyzed and estimated for the year 2017 with three different scenarios including 1) BAU (business as usual), 2) BACT (best available control technology) and 3) (BACT+ACT) (combination of best available control technology and advanced combustion technology). The co-benefits in this study include air quality benefit (reduction in pollutant emission) and climate benefit (reduction in GHGs, short-lived climate forcers and ground level ozone potential). The results of air quality benefit show that under 2017-BACT scenario the emission reduction of NOx would be by 85% and the emissions of other pollutants keep same as compared to 2017-BAU scenario, while the 2017-(BACT+ACT) scenario would result in reduction by 4% for SPM, PM10, PM2.5, COb2(B, SOb2 (Band VOCs, 3% for OC and BC, and 88% for NOx. The climate co-benefit analysis suggests that 2017-BACT scenario has reduced global warming potential in COb2 (Bequivalent by 0.3% for 20-year horizon and by 0% for 100-year horizon and 2017-(BACT+ACT) scenario has reduced that by 7% for 20-year horizon and by 4% for 100-year horizon, compared to that in 2017-BAU. It also suggests that the ozone formation contribution of the 2017-BACT scenario is 85% lower and that of 2017-(BACT+ACT) scenario is 88% lower than the 2017-BAU scenario for both 20-year and 100-year time horizon. s
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Air quality -- China; Climatic changes -- China; Coal-fired power plants -- China